2018
DOI: 10.5603/fm.a2017.0079
|View full text |Cite
|
Sign up to set email alerts
|

How automated image analysis techniques help scientists in species identification and classification?

Abstract: Identification of taxonomy at a specific level is time consuming and reliant upon expert ecologists. Hence the demand for automated species identification incre-ased over the last two decades. Automation of data classification is primarily focussed on images while incorporating and analysing image data has recently become easier due to developments in computational technology. Research ef-forts on identification of species include specimens' image processing, extraction of identical features, followed by class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 80 publications
(133 reference statements)
0
3
0
Order By: Relevance
“…In parallel, newly emerging supporting technologies are becoming increasingly affordable and accessible. These include various omics‐based applications, microbiomics, metabarcoding (Pawlowski et al ., 2018), automated species identification technologies (Gorsky et al ., 2010; Le Bourg et al ., 2015; Kalafi, Town & Dillon, 2018; Wäldchen & Mäder, 2018, First et al ., 2021), in vitro technology (Rosner et al ., 2021), bioinformatics, big data processing techniques and increased computing power. Omics technologies will facilitate studies on non‐model organisms; in vitro technology will enable the simultaneous analysis of samples from many species using a large number of tests; while technologies like DNA barcoding (Weigand et al ., 2019; Paz & Rinkevich, 2021) and automated species identification will reduce reliance on professional taxonomists, facilitating the processing of large amounts of data originating from (eco)toxicological tests performed on a variety of aquatic species.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, newly emerging supporting technologies are becoming increasingly affordable and accessible. These include various omics‐based applications, microbiomics, metabarcoding (Pawlowski et al ., 2018), automated species identification technologies (Gorsky et al ., 2010; Le Bourg et al ., 2015; Kalafi, Town & Dillon, 2018; Wäldchen & Mäder, 2018, First et al ., 2021), in vitro technology (Rosner et al ., 2021), bioinformatics, big data processing techniques and increased computing power. Omics technologies will facilitate studies on non‐model organisms; in vitro technology will enable the simultaneous analysis of samples from many species using a large number of tests; while technologies like DNA barcoding (Weigand et al ., 2019; Paz & Rinkevich, 2021) and automated species identification will reduce reliance on professional taxonomists, facilitating the processing of large amounts of data originating from (eco)toxicological tests performed on a variety of aquatic species.…”
Section: Discussionmentioning
confidence: 99%
“…Taxonomists' eagerness to reduce the time consumed for analysing samples (Benfield et al, 2007) and to significantly cut down the costs (Kalafi et al, 2018) were the main reasons that influenced the development of image-based identification systems. Culverhouse et al (2003) have shown that categorizing specimens from species that have significant variations in their morphology is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…With such obvious problems and various difficulties faced by researchers with manual identifications, automated identification systems seem to offer a possible solution. The idea of automated identification is not novel since it has been developed in various biological organisms previously (Abu et al 2013a(Abu et al , 2013bLeow et al 2015;Kalafi et al 2016;Morwenna et al 2016;Salimi et al 2016;Wong et al 2016;Kalafi et al 2017). Several classification methods such as neural network, structural, fuzzy and transform-based techniques have been used in biological image identification systems.…”
Section: Introductionmentioning
confidence: 99%